Axial-Flux Synchronous Machines Compared with Different Stator Structures for Use in Working - (:unkn) unknown (WYDAWNICTWO SIGMA-N O T SP Z O O, 2012)
In this study, three different stator topologies were investigated and compared utilizing 3D magnetic analysis, analytical calculations, and experimental studies. These stator structures are torus iron core: There have been far fewer studies based on slotless stator torus axial-flux permanent magnets (TAFPM-NS). Comparisons of simulated and measured values on prototype machines are also presented to validate the analyses.
Keywords: Torus axial flux permanent magnet machines (TAFPM); finite element analysis (FEA); electric generators